2. ANALYSIS OF ENGINE PYLON STRUCTURAL FAILURE AND ITS IMPACT ON FLIGHT SAFETY:CASE STUDY OF MD-11F (N259UP) - Ahmad Ilham Kamal; Ferdy Sastria; Feti Fatonah; Djoko Herwanto; Desiana Putri; Dikasitama; Muchammad furqon M (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to analyze the catastrophic structural failure experienced bya UPS McDonnell Douglas MD-11F (N259UP) cargo aircraft on November 4, 2025, inLouisville, Kentucky. The investigation focused on the detachment of the number 1 enginedue to engine pylon failure during takeoff. Through metallurgical analysis and a review ofthe NTSB investigation report, fatigue cracking in the forward mount fitting was found to bethe primary cause of the engine detachment. The results revealed gaps in routineinspection methods for aging aircraft. The study concluded that transitioning to StructuralHealth Monitoring technology and fleet modernization are crucial risk mitigation measuresfor the global air cargo industry.